Encrusted Cystitis: A Rare Morbid Disease - Rahul Gupta; Yasir Mehmood; Arti Mahajan; Sindhu Sharma (Journal of Mid-Life Health)
Encrusted cystitis (EC) is a rare clinical entity, with the first description dating back to 1914 by Francois J. This variety of debilitating and rare cystitis is caused by urea-splitting Corynebacterium urealyticum, especially Corynebacterium type 2B2 (CBGD2). Patients with prior urinary trauma, a history of intravesical bacillus Calmette–Guérin instillation, or chemotherapy are at higher risk for developing EC. Clinical presentation varies from dysuria, pain, hematuria, or passage of mucus or calcified mucopurulent stones. Diagnosis of Encrusted cystitis is done after excluding the other pathologies and is confirmed on isolation of Corynebacterium Type 2B2 organism and its characteristic features on radiotherapy. Medical management involves glycopeptide antibiotics and acidification of urine, either topical or systemic. Surgical treatment is done in rare cases with failed medical management or spontaneous bladder rupture. We report a rare case of morbid EC who required cystectomy and diversion.